Novel 3-aminobenzofuran derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Hasanvand, Zaman; Motahari, Rasoul; Nadri, Hamid; Moghimi, Setareh; Foroumadi, Roham; Ayati, Adileh; Akbarzadeh, Tahmineh; Bukhari, Syed Nasir Abbas; Foroumadi, Alireza (Frontiers in Chemistry, 2022)
A novel multifunctional series of 3-aminobenzofuran derivatives 5a-p were designed and synthesized as potent inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). The target compounds 5a-p were synthesized via three step reaction started from 2-hydroxy benzonitrile. In-vitro anti-cholinesterase activity exhibited that most of compounds have potent acetyl- and butyryl cholinesterase inhibitory activity. In particular, compound 5f containing 2-fluorobenzyl moiety showed the best inhibitory activity. Furthermore, this compound showed inhibitory activity on self and AChE-induced Aβ-aggregation and neuroprotectivity against PC12 cells. The kinetic study revealed that compound 5f has showed mixed-type inhibition on AChE, binding simultaneously to peripheral anionic site (PAS) and catalytic active site (CAS) of AChE. Based on these results, compound 5f can be considered as a novel multifunctional structural unit against Alzheimer’s disease.